Formation of Ecosystem Marketing Concept - SEKERIN, V. D.; GORLEVSKAYA, L. E.; GUSOV, A. Z.; GOROKHOVA, A. E. (Journal of Environmental Management and Tourism, 2018)
Economic ecosystems were considered in the paper. The concept of ecosystem marketing was proposed and disclosed. The effective functioning of ecosystems facilitates mutual with the consumer and other interested parties creation of values, allows working quicker with less expenditures, with risk sharing, making reasonable decisions in the real time mode. Application of the concept of ecosystem marketing allows companies to gain competitive advantages under conditions of turbulent medium. The classification of ecosystems was proposed in such directions as business, socium, state and science. An ecosystem approach in marketing allows building effective interactions and acts as a way of achieving goals. The authors substantiated the formation of ecosystem flexibility as a strategic goal of the ecosystem marketing. The developed methodology of calculating the ecosystems’ flexibility allows assessing their flexibility at different levels.